2024
DOI: 10.3390/plants13060758
|View full text |Cite
|
Sign up to set email alerts
|

Crop Landraces and Indigenous Varieties: A Valuable Source of Genes for Plant Breeding

Efstathia Lazaridi,
Aliki Kapazoglou,
Maria Gerakari
et al.

Abstract: Landraces and indigenous varieties comprise valuable sources of crop species diversity. Their utilization in plant breeding may lead to increased yield and enhanced quality traits, as well as resilience to various abiotic and biotic stresses. Recently, new approaches based on the rapid advancement of genomic technologies such as deciphering of pangenomes, multi-omics tools, marker-assisted selection (MAS), genome-wide association studies (GWAS), and CRISPR/Cas9 gene editing greatly facilitated the exploitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 216 publications
0
2
0
Order By: Relevance
“…Although NMR metabolite profiling is currently considered a reliable approach for the assessment of presence and relative abundance of small molecules [27,29,81,82], genetic information is, at present, the only method that provides a final validation with respect to the description of plant ecotypes [83][84][85][86]. Further studies will be needed to explore genetic information, thus providing a more comprehensive characterization of the Vessalico ecotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although NMR metabolite profiling is currently considered a reliable approach for the assessment of presence and relative abundance of small molecules [27,29,81,82], genetic information is, at present, the only method that provides a final validation with respect to the description of plant ecotypes [83][84][85][86]. Further studies will be needed to explore genetic information, thus providing a more comprehensive characterization of the Vessalico ecotype.…”
Section: Discussionmentioning
confidence: 99%
“…Native to the Pacific shore of South America [73], successfully domesticated in Mediterranean countries (Italy and Spain) and cultivated in marginal lands and under diverse microclimates, tomato landraces are considered a valuable genetic material for increased stress resilience, adaptability to low-input farming systems, and fruit quality [74][75][76]. Recent studies have revealed high economic profitability coupled with increases in sustainability through cultivation of landraces [77], encouraging their exploration, utilization, and even promotion in local food systems as an emerging management strategy [78,79] for agricultural systems with increased resilience and sustainability [80]. Nevertheless, modern varieties frequently demonstrate higher productivity than landraces.…”
Section: Introductionmentioning
confidence: 99%